Biblioteka pedagogiczna w środowisku lokalnym. Komunikat - Ippoldt, Lidia (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Pedagogical libraries meet the specific needs of a particular group of users. As a network, they have always played an extremely important role in the initial education, continued education, and professional development, as well as in the scientific and auto-didactic work of teachers. The regulation of the Minister of National Education of 28 February 2013 imposes the following tasks on pedagogical libraries: to organise and support schools and school libraries in carrying out their activities. These tasks can be divided into two groups: planning and carrying out activities aimed at improving the quality of work in relation to the needs of the school, and the organisation of networks and related cooperation and self-education for teachers, based on improvement, exchange of experience and best practices. The development of libraries gives librarians the incentive to constantly train, learn new methods and techniques for working with users, most of whom belong to the educational community. The pedagogical library is a service institution that also cares about its image. The image will decide whether the pedagogical library will become a link in the local education system for the local community.